Efficacies and Toxicities of Seven Chemotherapy Regimens for Advanced Hodgkin Lymphoma - Pei, Fajun; Yu, Yang; Dong, Bin; Guan, Hui; Dong, Xinzhe; Zhao, Fen (Frontiers in Pharmacology, 2021)
Background/Aims: Hodgkin Lymphoma (HL) has become one of the most treatable cancers, with more than 80% patients in the advanced stage being cured through improvement of therapeutic regimens. Nevertheless, some treatments were accompanied with toxicities. Methods: In the current study, a network meta-analysis (NMA) was conducted to compare the efficacies and toxicities of different chemotherapy regimens for advanced Hodgkin lymphoma (HL). We reviewed PubMed and EMBASE databases from inception to May 2018, and identified randomized controlled trials (RCTs) in which advanced HL patients received chemotherapy. Fourteen eligible RCTs published between 1992 and 2017 were enrolled in this NMA. These studies included a total of 5,964 HL patients, and assessed at least one of seven different chemotherapy regimens. Direct and indirect evidence was combined to calculate odds ratios (ORs) and 95% confidence intervals (95% CIs), and to establish a surface under the cumulative ranking (SUCRA) curve. Results: A cluster analysis was performed to evaluate efficacies and toxicities of different regimens. The COPP + ABVD (cyclophosphamide + vincristine + procarbazine + prednisone + doxorubicin + bleomycin + vinblastine + dacarbazine) regimen had the highest SUCRA partial response and overall remission rate values, while the ABVD regimen resulted in the lowest incidences of anemia, thrombocytopenia, neutropenia, and leucopenia. Conclusion: Cluster analysis revealed that COPP + ABVD had the best efficacy against advanced HL among the seven regimens, and ABVD had the lowest toxicity.